'The architecture of a probation office: A reflection of policy and an impact on practice': A practitioner response. (March 2015) - Harrison, Tom
This article is in response to Jake Phillips' article 'The architecture of a probation office: A reflection of policy and an impact on practice' (Phillips, 2014 ). The author addresses a topic which has had little attention in probation. Working environments are much talked about by probation staff but this operates mainly at a local and immediate level: noise, decoration, location, mobility, technology, ergonomics, etc. Phillips broadens out the discussion to look at how changes to probation's physical environment may be contributing to a 'them and us' attitude in staff towards their clients which runs counter to the current trend towards greater professional judgement and offender engagement. This article seeks to contribute to that debate by offering a practitioner's view and exploring the use of other perspectives to gain a greater understanding of the impact of our working environments on probation practice.